Biocontrol of rice sheath blight with formulated Pseudomonas putida - S.S GNANAMANICKAM, K. KRISHNAMURTHY and (Indian Phytopathology, 2002)
The development of an effective formulation for the biological control agent of sheath blight (Rhizoctonia solani) of rice, P. putida PpV14i, to increase shelf-life was investigated. Of the various combinations tested, methyl cellulose:talc in the ratio 1:4 was found to maintain the bacterium in a viable state for up to 10 months, affording 60% suppression of sheath blight of rice (cv. IR 50) in field experiments conducted at Pallikaranai, Tamil Nadu, India, which is on par with the fungicide validamycin. In addition, the formulation had no adverse effects on seed germination. The results were consistent when tested by the detached leaf assay in vitro.